En la salsa me quedo (2025)
The project focused on composing, adapting, and interpreting the musical genres of Son Montuno, Guaguancó, and Bolero within the context of salsa. Two original compositions, "Morena" and "Guaguancó Raro," were created, showcasing the project's innovation and creative prowess. Additionally, adaptations of Soda Stereo's "La Ciudad de la Furia" and El Caribefunk's "Chamuyera" were made to fit the target genres, demonstrating music's ability to transcend cultural boundaries. Various tools and resources were utilized, including musical elements from notable compositions and detailed transcriptions. The project delved into experimentation within the confines of established genres, paying homage to salsa tradition while exploring new avenues of expression and creativity.